Identifying the Factor that Promotes Vertical Partner-ships: Empirical Evidence from Tier-1 and Tier-2 Compa-nies in Jabodetabek-Indonesia - Syah, Donny Oktavian (Indonesian Journal of Science and Technology, 2019)
Indonesian automotive sector played an important role to Indonesian GDPs; it contributes 28% in manufacturing composition. The goal of this research is to examine the vertical partnership between tier-1 and tier-2 automotive component companies in Jabodetabek, Indonesia, as concerns technology transfer, technical exchange, government role, and supplier performance. 93 companies, consisting of 59 tier-1 companies and 34 tier-2 companies became respondents in this study. The research was conducted by visiting sites and interviewing companies, based on Likert-scale questionnaires. Interviewees were persons at the middle management level or higher who understood or were responsible for measuring product quality (purposive sampling). The results of questionnaires were proceeded and analyzed by Structural Equation Model Partial Least Square (SEM-PLS) path modeling using smart-PLS 3.2.7 software. The results showed that there is a significant relationship between the government’s role and technology transfer, as well as between technology transfer and supplier performance improvement. However, there was no significant relationship between government role and supplier performance improvement, nor between technical exchange and supplier performance improvement.